Joint trajectories of internalizing and externalizing problems in preschool children with autism spectrum disorder. (5th February 2016) - Vaillancourt, Tracy; Haltigan, John D.; Smith, Isabel; Zwaigenbaum, Lonnie; Szatmari, Peter; Fombonne, Eric; Waddell, Charlotte; Duku, Eric; Mirenda, Pat; Georgiades, Stelios; Bennett, Teresa; Volden, Joanne; et al.
Abstract: The co-occurring development of internalizing and externalizing problems were examined in an inception cohort of 392 children diagnosed with autism spectrum disorder at age 3 who were assessed on four occasions. Results indicated that internalizing and externalizing problems were stable over time and highly comorbid. Joint trajectory analysis suggested that 13% of the sample followed a dual high-risk trajectory. High risk was not found to be associated with intellectual ability or autism spectrum disorder symptom severity but was linked to lower income and gender: more girls than boys were found in the high/stable internalizing problems trajectory. The results suggest that 1 in 4 preschoolers followed a trajectory of internalizing or externalizing problems (or a combination of the two) that could be characterized as clinically elevated.